“It’s a delicate balance”: clinicians’ experiences of providing heroin-assisted treatment - Rune Ellefsen; Silvana De Pirro; Vegard Haukland; Linda Elise Couëssurel Wüsthoff; Espen Ajo Arnevik (Harm Reduction Journal)
Abstract Background Little attention has been paid to the experiences of clinicians and health personnel who provide heroin-assisted treatment (HAT). This study provides the first empirical findings about the clinicians’ experiences of providing HAT in the Norwegian context. Methods 23 qualitative interviews were conducted with 31 clinicians shortly after HAT clinics opened in Norway’s two largest cities: Oslo and Bergen. By inductive thematic analysis of interview transcripts, we identified what research participants experienced and viewed as the chief rewards and challenges of providing HAT. The study aimed to offer an overview of these key rewards and challenges, with insights potentially transferable to HAT programs internationally. Results Participants experienced three aspects of providing HAT as particularly rewarding, and three as most challenging. The rewarding aspects were observing harm reduction outcomes; providing holistic care; and having a positive clinic milieu and patient–clinician relationships. The challenging aspects were dosing and overdose risk; rule enforcement and aggression management; and the difficulty of initiating treatments beyond medication and harm reduction. The rewarding and challenging aspects of providing HAT overlapped and were at times contradictory, thus reflecting the duality and tensions in clinicians’ work to provide HAT. The challenges were reported to vary between patient subgroups, according to their degree of instability. The most unstable patients were seen as involving more difficulties as regards the challenging aspects of HAT. Participants expressed uncertainty about HAT’s utility for a small group of the most unstable patients. Conclusion While studies about clinical experiences of HAT have usually examined individual or limited aspects of treatment provision, this study provided an overview of the main aspects of the rewards and challenges of providing HAT. Importantly, it also showed the tensions between these overlapping and sometimes contradictory aspects of HAT provision. Because a positive patient–clinician relationship is crucial to patient satisfaction and treatment outcomes in HAT, the provision of training for clinicians on navigating the inherent tensions of HAT provision, nurturing therapeutic alliances with patients, and managing their role as gatekeepers to medical heroin and valuable services, seem particularly important for ensuring that care is patient-centered and staff are adequately supported.